TRANSFORMING GOVERNANCE: THE IMPACT OF ARTIFICIAL INTELLIGENCE ON INDIAN PUBLIC ADMINISTRATION - Pandey, Akshita; Shakya, Munindra Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The emergence of Artificial Intelligence (AI) has brought metamorphic changes across spectrum of sectors globally, and public administration also has not remained untouched. As the nation continues to digitize its governance mechanisms under initiatives like Digital India, India Stack, and the National Strategy for Artificial Intelligence, AI has emerged as a key enabler in redefining public service delivery, administrative efficiency, and policy formulation (NITI Aayog, 2018). This paper explores the multi-dimensional effects of AI on the functioning of public administration in India, such as enforcement of law, healthcare, policy and decision making, education, environment monitoring. This paper discusses various case studies like FASTag (National Highways Authority of India, 2021), AI-powered chatbots like MyGov Helpdesk, and Aarogya Setu (Ministry of Electronics and IT, 2020), through which this paper tries to highlight on how the AI helps the public administration in better execution of the policies of the government, in connecting with people and take their valuable feedback for the services. At the same time, the research examines the challenges including the algorithmic bias, data privacy concerns (OECD, 2021), the digital divide (World Bank, 2022) and the institutional resistance, all of which could hinder the adoption of AI if not addressed. This study explores the motivations of Government of India towards ethical and inclusive development of AI through public private partnerships, policy arbitration, and heavy investments in AI research (NITI Aayog, 2021). This study concludes by emphasizing that the Adoption of AI into the public administration, it must be implemented with a citizen centric approach, by reducing opacity in the processes and increasing accountability. This requires not just innovation in technology but also a shift in perspective towards functioning of bureaucracy of India.